Warfarin Dosing in a Patient with CYP2C9*3*3 and VKORC1-1639 AA Genotypes - Mark Johnson; Craig Richard; Renee Bogdan; Robert Kidd (Case Reports in Genetics)
Genetic factors most correlated with warfarin dose requirements are variations in the genes encoding the enzymes cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase (VKOR). Patients receiving warfarin who possess one or more genetic variations in CYP2C9 and VKORC1 are at increased risk of adverse drug events and require significant dose reductions to achieve a therapeutic international normalized ratio (INR). A 74-year-old white female with atrial fibrillation was initiated on a warfarin dose of 2 mg PO daily, which resulted in multiple elevated INR measurements and three clinically significant hemorrhagic events and four vitamin K antidote treatments over a period of less than two weeks. Genetic analysis later revealed that she had the homozygous variant genotypes of CYP2C9*3*3 and VKORC1-1639 AA. Warfarin dosing was subsequently restarted and stabilized at 0.5 mg PO daily with therapeutic INRs. This is the first case report of a white female with these genotypes stabilized on warfarin, and it highlights the value of pharmacogenetic testing prior to the initiation of warfarin therapy to maximize efficacy and minimize the risk of adverse drug events.